Pengaruh Promosi Penjualan Trade-In terhadap Minat Beli Bright Gas (Studi Kota Bandung) - Rahmawati, Putri Hasifah; Tiorida, Ermina; Raharso, Sri (REVITALISASI : Jurnal Ilmu Manajemen, 2025)
The use of non-subsidized LPG, Bright Gas, designated for middle and upper income households, always decreases every year, on the other side the use of LPG subsidized 3 Kg has increased. This condition indicates the low interest in buying bright gas in the community. One of the ways to increase the use of Bright Gas is by utilizing sales promotion programs, considering the long price difference between Bright Gas and LPG 3 Kg. This study aims to analyze the effect of trade-in sales promotion on Bright Gas buying interest among upper middle-income households in Bandung city. This study used quantitative methods with 183 samples determined using purposive sampling techniques, simple linear regression analysis was used in this study with the aid of SPSS software to measure the strength of the relationship between the variables in the study. The findings in this study show that trade-in sales promotion has a significant positive effect on Bright Gas buying interest.